A new genus and a new species of Sminthuridae (Collembola: Symphypleona) from Atlantic Forest of Brazil - Da Silva, Diego Dias; Palacios-Vargas, José G.; Bellini, Bruno Cavalcante (Zootaxa, 2015)
Sminthuridae comprises approximately 240 species distributed worldwide. In Brazil it is represented only by 11 species and four genera. Herein we describe a new genus and species of subfamily Sminthurinae from Atlantic Forest of Rio Grande do Norte State, Northeastern Brazil. The new described genus is similar to Gisinurus, Songhaica, Dietersminthurus and Soqotrasminthurus, especially in its unguis shape, with open cavity; but differs from all other genera of Sminthuridae by the presence of a single pretarsal chaeta in anterior side, smooth mucronal edges and a unique head chaetotaxy.